Peran Orang Tua dalam Menumbuhkan Minat Belajar Siswa pada Pembelajaran Daring di SDN Kamulan 01 Kecamatan Talun Kabupaten Blitar - Ria Fajrin Rizqy Ana (Universitas Kanjuruhan Malang, 2021)
The purpose of this study was to analyze the role of parents in fostering student interest in online learning at SDN Kamulan 01. The type of research used was qualitative research with a case study approach. The subjects in this study were parents and fifth grade students of SDN Kamulan 01, totaling 25 students. Data collection techniques using questionnaires, interviews, and documentation methods. Based on the results of the study, it was concluded that the role of parents was indispensable in fostering student interest in learning. The role of parents in fostering student interest in learning shows a total score of 1014 with a percentage of 85% and is in the very high category. Students' learning interest in online learning shows a total score of 765 with a percentage of 77% and is included in the high category.